The perspective of apprentices in the monitoring of vocational education and training policy : a comparative analysis of Denmark, Germany and Switzerland - Hippach-Schneider, Ute [Verfasser]; Grobe-Rath, Janine [Verfasser] (My University, 2024)
"Monitoring is an important building block for evidence-based VET policy. The regular surveying of key indicators relating to the VET system delivers valuable impetuses for educational policy decisions. But to what extent is the apprentices’ perspective taken into account? This article presents how the point of view of apprentices is systematically recorded via surveys in the three countries. Differences between the approaches in the countries of comparison become evident." (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; P 2.3 Auszubildende; I 2.2.1 Westeuropa; 370; Berufsbildungspolitik; Monitoring; Auszubildender; Subjektorientierung; Internationaler Vergleich; Dänemark; Schweiz; Bundesrepublik Deutschland